2020
DOI: 10.3390/microorganisms8091279
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Heteroresistance among Extended Spectrum β-lactamases-Producing Klebsiella pneumoniae

Abstract: Colistin-heteroresistant (CST-HR) Enterobacterales isolates have been identified recently, challenging the clinical laboratories since routine susceptibility tests fail to detect this phenotype. In this work we describe the first CST-HR phenotype in extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae isolates in South America. Additionally, we determine the genomic mechanisms of colistin heteroresistance in these strains. The CST-HR phenotype was analyzed by the population analysis profile (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…In our study, among the three MDR CH K. pneumoniae strains identified by PAP assays, two of them belong to ST15 and ST323, which are known multi-drug-resistant clones. Similarly, there are also other studies, where CH isolates belonging to well-known multidrug-resistant international lineages such as ST11, ST307 were identified [24,[29][30][31][32]. The association of colistin heteroresistance with isolates belonging to MDR clones which are known to be globally disseminated is very worrying since infections due to such strains are more likely to be treated with colistin if these are misclassified as susceptible by clinical diagnostic testing.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, among the three MDR CH K. pneumoniae strains identified by PAP assays, two of them belong to ST15 and ST323, which are known multi-drug-resistant clones. Similarly, there are also other studies, where CH isolates belonging to well-known multidrug-resistant international lineages such as ST11, ST307 were identified [24,[29][30][31][32]. The association of colistin heteroresistance with isolates belonging to MDR clones which are known to be globally disseminated is very worrying since infections due to such strains are more likely to be treated with colistin if these are misclassified as susceptible by clinical diagnostic testing.…”
Section: Discussionmentioning
confidence: 83%
“…A strength of this study was its large sample size compared to previous studies on CHR using the PAP assay [ 22 , 23 , 24 , 25 ]. Within this study, two different classification schemes for CHR were used.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that an amino acid change in the sensor domain of PhoQ or PhoQ overexpression may lead to the constitutive phosphorylation of PhoP, and the subsequent activation of genes involved in lipid A modifications [ 51 ]. Colistin heteroresistance in K. pneumoniae was also attributed to mutations in the pmrAB genes, encoding another two-component system that controls the synthesis of L-Ara4N and PEtN ( Figure 2 ) [ 21 , 56 , 57 ]. It is worth noting that diverse resistant subpopulations with different amino acid substitutions in PhoPQ and PmrAB were detected in various isolates.…”
Section: Prevalence and Mechanisms Of Heteroresistance In K Pneumoniaementioning
confidence: 99%
“…Other studies have found that clinical crrB mutations lead to the addition of both L-Ara4N and pEtN to lipid A, inducing higher polymyxin resistance [ 69 ]. Colistin resistance may also be linked to mutations, insertions, or deletions in the mgrB , yciM , and lpxM genes [ 44 , 51 , 53 , 57 ]. The mgrB gene encodes a small transmembrane protein which acts as a negative regulator of the PhoPQ system.…”
Section: Prevalence and Mechanisms Of Heteroresistance In K Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation